1988
DOI: 10.4141/cjas88-016
|View full text |Cite
|
Sign up to set email alerts
|

Procedure for Measuring Resting and Summit Metabolism in Sheep and Calves

Abstract: For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…To achieve body hypothermia of30"C, the water temperature was rapidly reduced to 28"C where it was held for 30 min, and then dropped to l8'C. (Young et al 1988). This system was calibrated by the N2 injection method (Young et al 1984) and the rate of metabolic heat production in watts (W) was calculated from oxygen consumption over intervals of 2 min using the equation of Mclean (19'12 (Burton and Edholm 1955), and for adult sheep at 25'C (Bennett 1972 The difference in rate of rewarming of the lambs in 38oC water in the present trial versus the rate reported by Robinson et al (1986) for lambs with hypothermia of 30oC, could be explained by differences in thermal gradients between the animal's core and environment.…”
Section: Induction Of Hypothermia and Test Proceduresmentioning
confidence: 99%
“…To achieve body hypothermia of30"C, the water temperature was rapidly reduced to 28"C where it was held for 30 min, and then dropped to l8'C. (Young et al 1988). This system was calibrated by the N2 injection method (Young et al 1984) and the rate of metabolic heat production in watts (W) was calculated from oxygen consumption over intervals of 2 min using the equation of Mclean (19'12 (Burton and Edholm 1955), and for adult sheep at 25'C (Bennett 1972 The difference in rate of rewarming of the lambs in 38oC water in the present trial versus the rate reported by Robinson et al (1986) for lambs with hypothermia of 30oC, could be explained by differences in thermal gradients between the animal's core and environment.…”
Section: Induction Of Hypothermia and Test Proceduresmentioning
confidence: 99%
“…The accuracy of the gas exchange determination is further dependent on the ability of the system to measure gas composition and importantly, the total volume of the air moved through the respirometry system (Fernández et al 2012 a ). To obtain a fast response from the system in a short time period, masks or hoods enclosing only the animal's face or head in connection with open circuits have been frequently employed with ruminants (Young et al 1988; Takahashi & Young 1992; Puchala et al 2007). An open-circuit system attached to a face mask presents the lowest cost and it is best suited and sufficiently accurate for fast response applications for measurement of gas exchange in animals for a short period of time (Fernández et al 2012 a ).…”
Section: Discussionmentioning
confidence: 99%
“…Results from the experimental confirmation trial compare favourably with those from the literature (Young et al 1988 (Young et al 1988) or heat production during sleeping or during increased activity (Rumpler et al 1990). The animal can therefore be used as its own control.…”
mentioning
confidence: 55%
“…The phenomenon of decreased 02 consumption associated with the energetic cost of posture has been reported previously in sheep maintained either in a similar hood system or in a water bath (Summers et al 1988). The energetic cost of posture also has been reported by Young et al (1988).…”
mentioning
confidence: 80%